Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas dan Opini Audit Terhadap Audit Delay : (Studi Empiris pada Perusahaan Infrastrukur yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2019 – 2021) - Cinthya cinthya1 (Akuntansi Prima, 2023)
The time that elapses between the completion of the audit by the auditor and the closing date of the current year's books is referred to as audit delay. The duration of time required for an auditor to complete his audit can indicate an indication of a serious problem. The purpose of this study is to determine the effect on the duration of auditing time (audit delay) that can occur when assessed in terms of profitability, solvency, size of a company and the opinion issued by an auditor. The results of selecting the financial statements of each infrastructure company left 20 out of a total of 58 companies based on the purposive sampling method. In approaching the decision or conclusion of the study test results using a quantitative approach, classical assumption test, and multiple linear regression. The final results of this study on audit delay prove that company size and solvency variables partially show a negative but not significant effect, while profitability and audit opinion have a significant positive effect. Meanwhile, company size, profitability, solvency, and audit opinion simultaneously or together have an effect on audit delay.